Plan maestro de producción basado en programación lineal entera para una empresa de productos químicos - Yunuem Reyes Zotelo; Josefa Mula; Manuel Díaz-Madro\~nero; Eduardo Gutiérrez González (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
– In this work, we propose an integer linear programming model for production scheduling of a group of finished products with independent demand. The model for the master production scheduling (MPS) is designed by considering production and inventory costs, as well as the productive process constraints regarding installations and production times. The aim of the proposed model is the minimization of the costs involved; specifically, undertime and overtime costs of resources, as well as the consideration of a minimum service level related to the deferred demand. The validation of the model considers data belonging to the demand of each product in a 12-week planning horizon and compares five scenarios in which some characteristics of the system and different service levels are modified. Finally, the results obtained for each one of the scenarios expose the improvement obtained by the proposed model with regard to the current procedure in the studied company.
Keywords: C61; L00; 330; production planning; master production scheduling (MPS); integer linear programming; chemical industry